Glencoe world geography : a physical and cultural approach - Boehm, Richard G., Ph.D. (Glencoe/McGraw-Hill, 1995)
Looking at the world; The United States and Canada; Latin America; Europe; Russia and the Eurasian Republics; North Africa and Southwest Asia; Africa South of the Sahara; South Asia; East Asia; Southeast Asia; Australia, Oceania, and Antarctica.